Computational Hyperspectral Imaging Based on Dimension-Discriminative Low-Rank Tensor Recovery - Zhang, Shipeng; Wang, Lizhi; Fu, Ying; Zhong, Xiaoming; Huang, Hua (Proceedings / IEEE International Conference on Computer Vision, 2019)
Exploiting the prior information is fundamental for the image reconstruction in computational hyperspectral imaging. Existing methods usually unfold the 3D signal as a 1D vector and treat the prior information within different dimensions in an indiscriminative manner, which ignores the high-dimensionality nature of hyperspectral image (HSI) and thus results in poor quality reconstruction. In this paper, we propose to make full use of the high-dimensionality structure of the desired HSI to boost the reconstruction quality. We first build a high-order tensor by exploiting the nonlocal similarity in HSI. Then, we propose a dimension-discriminative low-rank tensor recovery (DLTR) model to characterize the structure prior adaptively in each dimension. By integrating the structure prior in DLTR with the system imaging process, we develop an optimization framework for HSI reconstruction, which is finally solved via the alternating minimization algorithm. Extensive experiments implemented with both synthetic and real data demonstrate that our method outperforms state-of-the-art methods.